Challenges in management and prognosis of pediatric intestinal pseudo-obstruction - Türer, Özlem Boybeyi; Soyer, Tutku; Özen, Hasan; Arslan, Umut Ece; Karnak, İbrahim; Tanyel, Feridun Cahit (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Pediatric intestinal pseudo-obstruction (PIPO) is the most severe form of intestinal dysmotility in children. The aim of the study is to present the cases with PIPO in order to discuss the diagnosis, management and prognosis of PIPO.Materials and Methods: We retrospectively analyzed the medical records of patients with PIPO between 2010 and 2018.Results: Seven cases were included. The admission age was 3 days-10 years. The complaints were abdominal distention and constipation in all cases. All cases passed meconium in first 48 hour. Upper GI series revealed slow transit in 6 cases and malrotation in 2 cases. Full thickness rectum biopsies revealed normal ganglion cells. Neurological examination revealed post-infectious pan-dysautonomy in 1 case. Two cases are under follow-up with ileostomy and TPN, one case is with enteral feeding and ileostomy, three cases are stable with pyridostigmine, enemas, and laxatives. One case was died because of sepsis. The prognosis was not significantly correlated with initial presentation time, lag time, presence of extra-intestinal manifestations (p>0.05). The prognosis was significantly better when fewer number of operations were performed (p=0.029)Conclusion: PIPO is a broad-spectrum disease group that is difficult to diagnose and treat. It is mandatory to rule out the secondary causes for diagnosis. The medical and surgical treatments are used to support nutritional status, prevent sepsis and restore intestinal motility. The prognosis was better when secondary causes were identified and fewer operations were performed.